THE EFFECT OF HORMONES ON PHYSIOLOGICAL AND PSYCHOLOGICAL ADAPTATIONS DURING PREGNANCY - Harja, Evelyn; T, Ria Yulianti; Ai'sah; Azzahra, Akmevi Carissa; Merlinda, Euis; Fadia, Putri; Wahyuni, Rinda Tri; Dewi, Vanesa Fitriana (Journal for Quality in Women's Health, 2023)
In this study the authors raised the title of "Changes in Hormone Physiology and Psychology during Pregnancy". This study aims to review the journals that the authors have chosen. The method used in this study was a literature review of the 9,810 results that appeared, then a review was carried out on the 31 selected journals. The results of this study are that the hormonal changes that occur during pregnancy are very complex and correlate with each other to support the growth and development of the fetus as well as the body's preparation for childbirth and breastfeeding. Understanding the physical and emotional changes experienced by women during pregnancy is essential to support proper pregnancy care and management.